Comparison of Early Definitive Fusion and Traditional Growing Rods in Early-onset Dystrophic Scoliosis in Neurofibromatosis Type 1: A Preliminary Report. Issue 10 (November 2020) - Tauchi, Ryoji; Kawakami, Noriaki; Suzuki, Teppei; Uno, Koki; Yamaguchi, Toru; Yanagida, Haruhisa; Yamamoto, Takuya; Murakami, Hideki; Demura, Satoru; Kotani, Toshiaki
Abstract : Background: Early definitive spinal fusion (EF) has been widely recommended to avoid spinal deformity progression for early-onset scoliosis (EOS) with neurofibromatosis type 1 (NF-1). In contrast, growing rod (GR) procedure has recently been recommended for EOS associated with the dystrophic type NF-1. However, no studies have compared the surgical outcomes between EF and GR procedure for EOS with NF-1. The purpose of this study was to compare the surgical outcomes of EF versus GR for early onset and dystrophic scoliosis with NF-1. Methods: This was a retrospective multicenter study; 26 EOS patients with dystrophic type of NF-1 who underwent EF (16 patients) or GR (10 patients) were investigated. We compared age at first surgery, fused levels, total number of surgeries, coronal major curve, complication rates, spinal height (T1-T12 and T1-S1 length), and forced vital capacity between the 2 groups. Results: The mean age at first surgery was 7.3 years in the EF and 5.8 years in the GR ( P <0.05). The mean follow-up period was 12.8 and 10.5 years, respectively. The 2 groups did not show significant differences in preoperative major Cobb angle (75.1 vs. 83.1 degrees), complication rate (53% vs. 60%), and increase rate of T1-T12 (20.0% vs. 30.4%). However, significant differences ( P <0.05) were recognized in fusion segments (13.9 vs. 15.8), total numbers of surgery (2.6 vs. 10.1), correction rate of major curve (59.0% vs. 40.6%), increase rate of T1-S1 (19.0% vs. 33.9%), body height at final follow-up (151 vs. 142 cm), and forced vital capacity at final follow-up (2.23 vs. 1.46 L). Conclusions: Early fusion is still a viable option for progressive EOS with dystrophic type of NF-1 even in the growth-friendly era. Surgeons should consider the best procedure for each patient taking into account the severity of dystrophic change when treating EOS with NF-1. Level of Evidence: Level IV.